The role of automation and robotics in transforming hydroponics and aquaponics to large scale - Milon Selvam Dennison; P. Sathish Kumar; Fwangmun Wamyil; M. Abisha Meji; T. Ganapathy (Discover Sustainability)
Abstract Automation and robotics are revolutionizing hydroponic and aquaponic farming techniques and also enhancing their efficiency, sustainability, and scalability within the Controlled Environment Agriculture (CEA). This review explores the integration of key technologies, such as automated nutrient and pH management systems, advanced lighting solutions, and IoT-enabled smart farming practices. These innovations significantly boost productivity, optimize resource utilization, and reduce labor dependency, although with challenges like high initial capital investment, technical complexity, and energy demands. The paper examines case studies showcasing improvements in yield and resource efficiency while addressing scalability and energy limitations. Emerging technologies, including AI-driven analytics and off-grid power solutions, are identified as promising avenues to overcome these hurdles. By presenting actionable insights and emphasizing the importance of energy-efficient equipment and sustainable practices, this review underscores the potential of automation and robotics to transform hydroponic and aquaponic systems. Ultimately, this work supports global food security, environmental conservation, and the advancement of circular economy principles. Clinical Trial This research does not involve clinical trials.